The Power of Brand Image, E-Service Quality towards Purchase Decisions on e-commerce in Indonesia - Hayati, Mardhiyah; Juhary, Ali; Suryanto, Tulus (2023)
This study is aimed to inspect a model, which has an influence on purchasing decisions taken by consumers in the province of Lampung Indonesia on an e-commerce platform. The results of this study indicate that brand image has a significant effect on purchasing decisions (0.327) and e-service quality takes a significant influence on purchasing decisions (0.405). Therefore, the ability to create, maintain, protect and enhance e-service quality together with brand image in expanding the scope of trade is the most important task for marketing.